Navigating the Complexities: Challenges in Diagnosing and Managing Constrictive Pericarditis - Singha, Chayan; Subedi, Subas (Bangladesh Journal of Medicine, 2024)
Constrictive pericarditis poses a diagnostic and management challenge due to its varied etiology and subtle clinical presentation. This study aimed to elucidate these complexities by analyzing a cohort of six patients diagnosed with constrictive pericarditis over one year. The mean duration of diagnosis was found to be one & half years, indicating significant delays in recognition. Tuberculosis was the predominant etiology observed in four patients, followed by COVID-19 in one, and idiopathic causes in one case. Remarkably, all patients, except two, experienced prolonged delays in diagnosis, underscoring the diagnostic challenges inherent in this condition. Despite all patients being candidates for radical pericardiectomy, only four underwent surgery with financial constraints preventing two from accessing surgical intervention. Tragically, one patient succumbed to operative complications, highlighting the risks associated with surgical intervention. However, the remaining operated patients are currently faring well, emphasizing the potential benefits of timely surgical management. This study underscores the importance of early recognition and appropriate management strategies in mitigating the morbidity and mortality associated with constrictive pericarditis. Further research is warranted to refine diagnostic algorithms and optimize therapeutic approaches for this challenging condition. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 175